A training guide for in-situ conservation on farm - Jarvis, Devra I.; Meyer, L.; Klemick, H.; Guarino, Luigi; Smale, Melinda; Brown, A.H.D.; Sadiki, M.; Sthapit, B.; Hodgkin, T.; International Plant Genetic Resources Institute (2000)
Version 1In-situ conservation on-farm is a diverse and complex topic, and as a result any training guide can not cover every detail of the disciplines involved. Instead, this guide is geared to give national programmes basic technical skills and tools to build institutional capacity and partnerships to implement an on-farm conservation programme. It discusses the information necessary and the practical steps for the implementation of on-farm conservation, as well as the importance of such an initiative. Equipped with the baseline information from this guide, the reader should then be able to identify and access more detailed information on specialized topics.